Bob Cuspe, without anesthesia: misunderstanding and hate in the rupture speech of an iconoclastic character - Barros, Ibere Moreno Rosario e; Barros, Laan Mendes de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2022)
Hate speech is handled in this work in an alternative way to approaches that question the violence, the denial and the exclusion of the other, in the search for overcoming conflicts. It assumes the idea of misunderstanding and confrontation, sarcastic criticism and aggressive speech as coping and resistance resources, as sensitive strategies adopted by subaltern segments of society that inhabit the opaque territories of the city. It starts from articulations between culture and counterculture, history and communication, aesthetics and politics, in the study of mediatized narratives, as is the case of comics and political cartoons. It brings to the analysis a clipping of the rupture speech proposed by the cartoonist Angeli, in the figure of an iconoclastic character, the subversive and aggressive Bob Cuspe, who confronts and challenges the neoliberal society with his ironic and blunt hate speech. For the purpose of to problematize and critically reflect on this issue, theoretical foundations are sought in readings by authors such as Jacques Ranciere, Gregoire Chamayou and Muniz Sodre.
Keywords: Comic strips; Counterculture; Communication without anesthesia; misunderstanding